The complexity of caffeine's effects on regular coffee consumers - Mateja Lesar; Jakob Sajovic; Dušanka Novaković; Maša Primožič; Eva Vetrih; Martin Sajovic; Anja Žnidaršič; Peter Rogelj; Andreas Daffertshofer; Zoran Levnajić; Gorazd Drevenšek (Heliyon)
Why does coffee wake us up? Is it because it contains caffeine, or because we are used to it waking us up after drinking it? To answer this question, we recruited twenty habitual coffee drinkers who received either caffeinated or decaffeinated coffee (placebo) in a double-blind, randomized fashion. The two substances were identical except for the presence of caffeine. We measured cognitive performance, cardiovascular responses, and whole-head EEG during rest and during an auditory-oddball task. The same measurements were done before and after ingestion. We expected to find significant differences between caffeine and placebo groups across the outcome measures. However, except for the resting-state alpha power, changes due to ingestion in physiological responses and in cognitive functioning were not significantly different between the two groups. Actually, only one of the three cognitive measures was found to be significantly altered by the ingestion. These findings suggest that regular coffee consumers respond to coffee-like beverages independently of the presence of caffeine.